PARATAXE ET HYPOTAXE DANS L’ACQUISITION DU FLE PAR DES APPRENANTS POLONOPHONES. APPROCHE LONGITUDINALE - Paprocka-Piotrowska, Urszula (Neofilolog, 2019)
This paper focuses on the acquisition of the second language (L2) and the development of syntactic competence in communication. The topic is discusses in relation to syntactic structure of narratives produced by Polish learners of French L2. The author observes in detail how language learners build simple and complex sentences (coordinating/subordinating conjunctions, complex/simple sentences ratio, para- and hypotactic sentence structures) at the three different moment of SLA: 6th, 12th and 35th month of their classroom learning/teaching (developmental and comparative approach).